Determinants of market participation among pineapple farmers in Aiyedaade Local Government Area, Osun State, Nigeria (2015)
This study examined the determinants of market participation among pineapple farmers in Aiyedaade Local overnment Area of Osun State, Nigeria. Interestingly, in spite of major constraints, such as bad roads, inadequate storage facilities, and low level of government support, almost all of the farmers participated in the market. This could be sustained if market centers are established at strategic locations not too far from farms and if loans are made accessible to the farmers with low interest rates requiring simplified procedures for processing. Intervention strategies for improvement of pineapple farmers’ market participation should also be guided by farmers age, farming experience, and marital status.